Assessment of the chemical solubility of experimental and commercial lithium silicate glass-ceramics - Vallerini, Bruna de F. [UNESP]; Pinelli, Ligia A.P. [UNESP]; Silva, Laís D.; Soares, Viviane O.; Peitl, Oscar; Zanotto, Edgar D.; França, Rodrigo (Elsevier, 2025)
Objective: This study aimed to evaluate the chemical solubility (CS) and conduct a comprehensive physicochemical characterization of several experimental and commercial lithium silicate-based glass-ceramics towards an understanding of the chemical processes governing dissolution in these glass-ceramics. Methodology: Glass-ceramic (GC) samples were categorized into two groups: experimental materials featuring lithium metasilicate crystals (GCE1 and GCE2); and five commercial brands relying mostly on lithium disilicate (Celtra®Duo, IPS e.max®CAD, Straumann®n!ce®, CEREC Tessera™, and VITA Suprinity®). CS was assessed by submerging samples in a 4 % acetic acid solution following ISO 6872 standards. High-resolution inductively coupled plasma mass spectrometry (HR-ICP-MS) was employed to evaluate ion leaching from the residual acetic acid solution. Surface roughness and chemical composition were scrutinized using Atomic Force Microscopy (AFM) and X-Ray Photoelectron Spectroscopy (XPS), respectively. Results: All groups met the CS standards. Kruskal-Wallis with the Dunn post-hoc test was used for CS, two-way ANOVA for roughness, and three-way ANOVA for XPS, each followed by Tukey's post-hoc test (α=0.05). AFM revealed no significant alteration in surface roughness post-immersion for the majority of the groups, except for IPS e.max®CAD (p < 0.001). XPS detected compositional changes in all GCs following CS testing. HR-ICP-MS indicated a higher leaching of Li+ ions (as expected) across all groups. Conclusion: This study supports the understanding of the chemical processes that govern the dissolution of glass-ceramics and evaluate how different formulations influenced the CS and elemental composition. In this sense, the GCE2 group exhibited the most favorable properties for dental applications, mirroring the performance of the main commercial materials.
Keywords: Atomic force microscopy; Dental Materials; Glass-Ceramics; Mass spectrometry; Photoelectron Spectroscopy; Solubility